Disruption of resting functional connectivity in Alzheimer's patients and at-risk subjects - Krajcovicova, Lenka; Marecek, Radek; Mikl, Michal; Rektorova, Irena (Current neurology and neuroscience reports, 2014)
The resting brain exhibits continuous intrinsic activity, which is correlated between groups of regions forming resting state networks. Evaluating resting connectivity is a popular approach for studying brain diseases. Several hundred studies are now available that address integrity of resting connectivity in patients with Alzheimer's disease (AD) and mild cognitive impairment (MCI), as well as preclinical at-risk subjects. Most studies focus on the default mode network, a system of specific brain areas showing strong connected resting activity that attenuates during goal-directed behavior. The extent of intrinsic brain activity tends to be strongly correlated with cognitive processes and is specifically disrupted in AD and MCI patients and at-risk subjects, with changes seeming to evolve during the transition between the disease stages. In this study, we review the current findings in default mode network and other resting state network studies in AD and MCI patients and at-risk subjects as assessed by resting state functional magnetic resonance imaging.
Keywords: nervové dráhy; rizikové faktory; Brain; Cognitive Dysfunction; Alzheimerova nemoc; Neural Pathways; Nerve Net; Alzheimer Disease; mozek; odpočinek; neurozobrazování; Humans; Neuroimaging; Rest; Risk Factors; nervová síť; kognitivní dysfunkce; lidé